Development of Multimedia Teaching Materials Through Multiliteration Based Video scribe and Camtasia Studio Applications in Elementary Schools - Setiawan, Sigit; Yuliana, Rina; Alamsyah, Trian Pamungkas (Jurnal Ilmiah Sekolah Dasar, 2020)
The low quality at each level and education unit is caused by a lack of learning media that helps students learn. This study aims to develop multimedia teaching materials through the video scribe and Camtasia study applications based on multiliterate elementary school students and to determine the feasibility and responses of students to multimedia teaching materials. This study used the R&D (Research and Development) research method with a modified Borg and Gall research design. The population in the limited trial numbered 20 students. The sampling technique used the purposive sampling technique. The data collection instruments in this study were observation sheets, questionnaire sheets, interviews, and documentation. The results showed that validation by media experts got 90.28% (very feasible), language experts 99.17% (very feasible), material experts 92.11% (very feasible). The results of the student response questionnaire in the field trial showed 96.41% with very feasible criteria. Based on these results, the final product in the form of multimedia teaching materials through the multiliterate-based videoscribe and Camtasia studio applications for elementary school students is very suitable for use for learning activities of fifth-grade elementary school students. The implication of this research is to provide learning media facilities in the form of multimedia teaching materials that can facilitate student learning needs.